Impact of hypoglycemic episodes on health-related quality of life of type-2 diabetes mellitus patients: development and validation of a specific QoLHYPO(©) questionnaire - Orozco-Beltrán, Domingo (Health Qual Life Outcomes, 2018)
BACKGROUND: Hypoglycemia is a limiting factor to achieving optimal glycemic control in patients with type-2 diabetes mellitus (T2DM), increasing risk of death and complications, reducing health-related quality of life (HRQoL) and work productivity and increasing healthcare costs. The study’s primary objective was to develop and validate a specific questionnaire to assess the impact of hypoglycemia on the HRQoL of T2DM patients (QoLHYPO(©) questionnaire). METHODS: A two-phase multicenter prospective, longitudinal, observational, epidemiologic study of consecutively enrolled patients, not involving any drug, was conducted: In phase 1 (questionnaire development), patients who had given their written informed consent, who were at least 30 years of age, had been diagnosed with T2DM at least 5 years prior, had an HbA1c test in the previous 3 months, and a hypoglycemic episode in the previous 6 months were included. To validate the questionnaire and assess reliability and responsiveness, phase 2 included two cohorts of patients. Patients in the reliability cohort would likely have stable clinical course during the 3 weeks following inclusion in the study and patients in the responsiveness cohort would likely experience changes in their clinical course in the 3 months after enrollment. RESULTS: Phase 1 included 168 patients: 10 attended semi-structured interviews, 18 for face validity, and 140 for the pilot test (Rasch analysis). Phase 2 included 227 patients: 142 in the reliability cohort and 85 in the responsiveness cohort. Of the 37 items initially included in Phase 1, 11 (floor/ceiling effect analysis) and 13 (Rasch analysis) were discarded. The final version of the questionnaire consisted of 13 items. Phase 2 results showed the questionnaire was unidimensional and able to accurately assess HRQoL. Intra-observer reproducibility (ICC = 0.920) and internal consistency (Cronbach’s alpha: visit 1 = 0.912; visit 2 = 0.901) were high, showing high reliability. Internal responsiveness was moderate (standardized effect size 0.5-0.8) and external responsiveness was lower (AUC > 0.5; not statistically significant). Minimal clinically important difference (MCID) was estimated to be 3.2 points. CONCLUSIONS: The QoLHYPO(©) questionnaire is a tool that can be used in routine clinical practice to assess the impact of hypoglycemia on the HRQoL of T2DM patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12955-018-0875-1) contains supplementary material, which is available to authorized users.